Dobiček in prostor - Bentley, Ian (Urbani izziv, 1997)
The article deals with the physical and symbolic effects the built environment has on human activities in a capitalist economy. The built environment is integrated in the capitalist economy on three levels: as the focus of a profit-oriented manufacturing industry, as the setting for all sorts of other enterprises and as the built context of the whole economy. The built environment is understood as a commodity. The capitalist system contains inbuilt tension which have important design implications: the first tension arises because the system, if left to itself, lacks any overall planning functions, the second tension items from the ability of the system to generate profit and the third arises from the character of labour, which distinguishes it from other commodities used in the production process. In conclusion methods of designing built environments which perpetuate social order are discussed.
Keywords: architecture; arhitektura; bivalno okolje; prostor; teorija arhitekture; urbanism; urbanizem